LATIN 2016 : theoretical informatics : 12th Latin American Symposium, Ensenada, Mexico, April 11-15, 2016, Proceedings /: theoretical informatics : 12th Latin American Symposium, Ensenada, Mexico, April 11-15, 2016, Proceedings. (2016) - Unknown
No abstract available